Review on Rasachandrika Rajavaidyam (International Journal of Ayurveda and Pharma Research, 2025)
Rasasastra is a specialized branch of Ayurveda that integrates ancient alchemical practices with traditional Ayurvedic practices, aiming to enhance health, longevity and spiritual wellness. The practice of Rasasastra varies from one region to another. While the origin of Rasasastra can be traced to ancient India with classical texts such as Rasarṇava and Rasaratna Samuccaya, Kerala has contributed significantly to the evolution of this discipline, particularly through the integration of local medicinal practices and influences from the Siddha system. Kerala’s Rasasastra is a unique blend of Ayurvedic and Siddha traditions. The close cultural and geographical proximity between Kerala and Tamil Nadu fostered significant interactions between Ayurveda and the Siddha system of medicine. Siddha, with its emphasis on the therapeutic and alchemical use of minerals, metals, and mercurial preparations, played a transformative role in shaping Kerala’s Rasasastra practices. Rasachandrika rajavaidya is a Rasasastra textbook written in Malayalam language, which mainly focus on the processing of Parada for therapeutic purposes. This manuscript is presented with guidelines of Parada bandhana with different Satwas. This textbook serves as an important reference text for Rasavaidyas for designing and development of drugs.